The Effectiveness of a Behavioral Program on Severity of Urinary Incontinence Among Iranian Women With Multiple Sclerosis - Mohammad Sahebalzamani; Sayedeh Zahra Hosseinigolafshani; Farnoosh Rashvand (Shahrekord University of Medical Sciences, 2017)
Background and aims: Urinary incontinence is common among multiple sclerosis (MS) patients, which affects their quality of life negatively. This study examined the effectiveness of a behavioral training program on severity of urinary incontinence among Iranian women with MS. Methods: This is a quasi experimental study. The sample was selected using purposeful sampling from all those who presented for routine follow-up care and treatment in an MS clinic in Tehran from March 2015 to September 2015. The training consisted of 2 sessions (each were 45 minutes) video, small group discussion and group lecture in which all aspects of the urinary incontinence were taught. Before the study initiation, patients were asked to complete the Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQUI-SF) and a demographic questionnaire. Three month after the first educational intervention, MS patients were reassessed using the ICIQUI-SF. Data analyzed in SPSS 21. Results: The mean total scores of ICIQ-SF were 12.4 ± 3.3 and 7.1 ± 3.2 before and after training, respectively. According to the results of paired t test, this difference before and after study was statistically significant (P<0.001). The mean scores of "number of urine leak" were 2.7 ± 0.9 and 1.5 ± 0.8 before and after intervention, respectively (P<0.001). The mean scores of "amount of urine leak" were 3.3 ± 1.4 and 2.1 ± 0.9 before and after intervention, respectively (P<0.001). The mean scores of "effect of urine leak on everyday life" were 6.3 ± 2.1 and 3.6 ± 2.0 before and after intervention, respectively (P<0.001). Conclusion: Behavioral training could be effective strategy in management of bladder dysfunction in MS patients. Health-care providers should be aware of this and plan for use. Further study in this regard is strongly recommended.